2019
DOI: 10.1002/adom.201801376
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for On‐Demand Dispersion Engineering of Waves in Metasurfaces

Abstract: IntroductionMetasurfaces and surface waves are two booming research branches in modern optics and wave physics. As 2D counterparts of 3D metamaterials, metasurfaces have inherited many unusual properties of artificially structured metamaterials, e.g., negative refraction, super-resolution imaging, and invisibility. [1][2][3][4][5][6] Nevertheless, owing to the reduced dimension, metasurfaces are much easier to fabricate, thus providing possibilities to transform theoretical innovations to practical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…[37] By studying the physical mechanisms of coupled SPPs, the concept of digital M-waves was brought forward. [10,48] Based on the novel properties of M-waves and dispersion engineering methodologies, [50,140] subdiffraction-optics and flat optics rapidly developed, which finally lead to the formation of catenary optics. Since it could break the fundamental limitations of classical optics, such as the diffraction limit and Snell's law, catenary optics may become one cornerstone of the next generation of engineering optics, which we refer to as engineering optics 2.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] By studying the physical mechanisms of coupled SPPs, the concept of digital M-waves was brought forward. [10,48] Based on the novel properties of M-waves and dispersion engineering methodologies, [50,140] subdiffraction-optics and flat optics rapidly developed, which finally lead to the formation of catenary optics. Since it could break the fundamental limitations of classical optics, such as the diffraction limit and Snell's law, catenary optics may become one cornerstone of the next generation of engineering optics, which we refer to as engineering optics 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…[135] In recent years, there have been many types of research devoted to realizing achromatic flat lenses. [50,[136][137][138][139][140]…”
Section: Generalized Laws Of Refraction and Reflectionmentioning
confidence: 99%
“…However, this approach is time‐consuming, especially for the design of metasurfaces that possess multispectral manipulation. Recently, the electric field distribution and frequency‐dependent dispersion of M‐waves in metallic nanostructures were demonstrated to be well described by a catenary model, and an analytic method derived from catenary EM field theory was concluded to simplify the design (see Part I in the Supporting Information for a detailed description of catenary EM field theory). As mentioned in our previous works, in the simplest case of 1D metallic slits, the electric field distribution is mainly determined by the gap width w of the slits when the thickness t of the metasurface is in the deep‐subwavelength range (i.e., t << λ).…”
Section: Design and Methodsmentioning
confidence: 99%
“…Thus far, many methods have been proposed to quantitatively optimize the EM response of metasurfaces . Recently, it was shown that the EM field distribution and frequency dispersion of meta‐surface‐waves (M‐waves) in a 1D metallic slit are well described by a catenary model, providing a useful way for simplifying the design of metasurface‐based devices …”
Section: Introductionmentioning
confidence: 99%
“…The progress in theory and technologies of nanophotonics, plasmonics, optics of metamaterials (MMs) and metasurfaces provided possibilities to reduce dimensions of many optical elements such as modulators, filters, absorbers, phase shifters, holograms, nanoresonators and others down to nanometer values (see, e.g. recent reviews [1][2][3][4][5][6][7][8][9][10][11][12] and numerous references in these works). The main purpose of such ultra-small devices is to control the radiation characteristics (amplitude, phase, polarization) at deeply subwavelength dimensions of a composite material or system.…”
Section: Introductionmentioning
confidence: 99%